Direct assembly of micron-size porous graphene spheres with a high density as supercapacitor materials. (August 2019) - Wei, Jie; Luo, Chong; Li, Huan; Lv, Wei; Liang, Jiachen; Deng, Yaqian; Huang, Zhijia; Wang, Cong; Kang, Feiyu; Yang, Quan-Hong
Abstract: A high volumetric energy density is extremely important in practical energy storage devices. Porous yet dense graphene monoliths obtained from a graphene hydrogel by capillary shrinkage are promising materials for achieving both high volumetric power and energy densities but they are hard to be further processed or ground into fine powders for use in industrial electrode fabrication. Here, by introducing an additional shaking process during the assembly, the bulk graphene hydrogel was broken into many graphene spheres of a much smaller size, and after capillary drying, micron-size graphene spheres were obtained with both a high density and high porosity. These microspheres were used to assemble an electrode with a higher density and give an improved volumetric energy density, which is very important for practical energy storage devices. Graphical abstract: Image 1